Understanding the Experiences of Remote Workers: Opportunities for Ambient Workspaces at Home - Margariti, Eleni Kallopi; Ali, Ridita; Benthem de Grave, Remco; Verweij, David; Smeddinck, Jan; Kirk, David (Frontiers in Computer Science, 2021)
As the COVID-19 pandemic has forced many to work remotely from home, collaborating solely through digital technologies, a growing population of remote home workers are faced with profound wellbeing challenges. Passive sensing devices and ambient feedback have great potential to support the wellbeing of the remote workers, but there is a lack of background and understanding of the domestic workplace in terms of physical and affective dimensions and challenges to wellbeing. There are profound research gaps on wellbeing in the domestic workplace, with the current push for remote home and hybrid working making this topic timely. To address these gaps and shape a starting point for an ‘ambient workspaces’ agenda, we conducted an exploratory study to map physical and affective aspects of working from home. The study involved both qualitative and quantitative measures of occupant experience, including sensor wristbands, and a custom web application for self-reporting mood and aspects of the environment. It included 13 participants for a period of 4 weeks, during a period of exclusive home working. Based on quantitative and qualitative analysis, our study addresses wellbeing challenges of the domestic workplace, establishes correlations between mood and physical aspects, and discusses the impact of feedback mechanisms in the domestic workplace on the behavior of remote workers. Insights from these observations are then used to inform a future design agenda for ambient technologies that supports the wellbeing of remote workers; addressing the design opportunities for ambient interventions in domestic workspaces. This work offers three contributions: (1) qualitatively and quantitatively informed understandings of the experiences of home-workers; (2) a future design agenda for ‘ambient home workspaces’; and (3) we propose three design concepts for ambient feedback and human – AI interactions in the built environment, to illustrate the utility of the design agenda.